Self-assembly of smallest magnetic particles - Mehdizadeh Taheri, Sara (Proc Natl Acad Sci U S A, 2015)
The assembly of tiny magnetic particles in external magnetic fields is important for many applications ranging from data storage to medical technologies. The development of ever smaller magnetic structures is restricted by a size limit, where the particles are just barely magnetic. For such particles we report the discovery of a kind of solution assembly hitherto unobserved, to our knowledge. The fact that the assembly occurs in solution is very relevant for applications, where magnetic nanoparticles are either solution-processed or are used in liquid biological environments. Induced by an external magnetic field, nanocubes spontaneously assemble into 1D chains, 2D monolayer sheets, and large 3D cuboids with almost perfect internal ordering. The self-assembly of the nanocubes can be elucidated considering the dipole–dipole interaction of small superparamagnetic particles. Complex 3D geometrical arrangements of the nanodipoles are obtained under the assumption that the orientation of magnetization is freely adjustable within the superlattice and tends to minimize the binding energy. On that basis the magnetic moment of the cuboids can be explained.